A multisynaptic pathway from the ventral midbrain toward spinal motoneurons in monkeys. (17th February 2022) - Suzuki, Michiaki; Inoue, Ken‐ichi; Nakagawa, Hiroshi; Ishida, Hiroaki; Kobayashi, Kenta; Isa, Tadashi; Takada, Masahiko; Nishimura, Yukio
Abstract : Abstract: Motivation boosts motor performance. Activity of the ventral midbrain (VM), consisting of the ventral tegmental area (VTA), the substantia nigra pars compacta (SNc) and the retrorubral field (RRF), plays an important role in processing motivation. However, little is known about the neural substrate bridging the VM and the spinal motor output. We hypothesized that the VM might exert a modulatory influence over the descending motor pathways. By retrograde transneuronal labelling with rabies virus, we demonstrated the existence of multisynaptic projections from the VM to the cervical enlargement in monkeys. The distribution pattern of spinal projection neurons in the VM exhibited a caudorostral gradient, in that the RRF and the caudal part of the SNc contained more retrogradely labelled neurons than the VTA and the rostral part of the SNc. Electrical stimulation of the VM induced muscle responses in the contralateral forelimb with a delay of a few milliseconds following the responses of the ipsilateral primary motor cortex (M1). The magnitude and number of evoked muscle responses were associated with the stimulus intensity and number of pulses. The muscle responses were diminished during M1 inactivation. Thus, the present study has identified a multisynaptic VM–spinal pathway that is mediated, at least in part, by the M1 and might play a pivotal role in modulatory control of the spinal motor output. Key points: Motivation to obtain reward is thought to boost motor performance, and activity in the ventral midbrain is important to the motivational process. Little is known about a neural substrate bridging the ventral midbrain and the spinal motor output. Retrograde trans‐synaptic experiments revealed that the ventral midbrain projects multisynaptically to the spinal cord in macaque monkeys. Ventral midbrain activation by electrical stimulation generated cortical activity in the motor cortex and forelimb muscle activity. A multisynaptic ventral midbrain–spinal pathway most probably plays a pivotal role in modulatory control of the spinal motor output. Abstract : Abstract figure legend We found a multisynaptic projection from the ventral midbrain (VM), consisting of the ventral tegmental area (VTA), substania nigra pars compacta (SNc) and retrorubral field (RRF), to the spinal cord in monkeys. There was a caudorostral gradient, in that the caudal VM (i.e. the caudal part of the SNc and RRF) contained more neurons projecting indirectly to the spinal cord than the rostral VM (i.e. the rostral part of the SNc and VTA). Activation of the VM induced responses in the primary motor cortex (M1) and several forelimb muscles. These muscle responses were mediated by M1. The VM might have a modulatory action on descending motor pathways.